Evaluation of Vocational Education Management in the Era of the Fourth Industrial Revolution and Society 5.0 at SMKN 2 Pengasih - Hastutiningsih, Arum Dwi; sugiyono, sugiyono; suyanto, suyanto; ashyrnepesov, vezir (Faculty of Engineering, Universitas Negeri Yogyakarta, 2024)
The era of industrial revolution 4.0 and society 5.0 has brought significant changes in various aspects of life, including in the world of vocational education. Vocational education is becoming increasingly important in this era because the business world and the industrial world (DUDI) increasingly need a skilled workforce and have skills that are relevant to industry needs. This study aims to find out how far the management of vocational education is in the era of the Industrial Revolution 4.0 and Society 5.0, especially at SMK N 2 Pengasih. The research was conducted using qualitative methods using interviews as a data collection technique. The results of the research show that the management of vocational education in the era of the industrial revolution 4.0 and society 5.0 at SMKN 2 Pengasih has been going quite well. However, there is still a need for improvement considering that there are still several obstacles in its implementation.Keywords: Industrial Revolution 4.0, Society 5.0, Vocational Education